13-14 JAS VOLEYBOL OYINSHILARINIŃ TEXNIK TAKTIK SHEBERLIGIN JETILISTIRIW - Qaljanov, R.P. (SCIENCE and SOCIETY, 2023)
The article describes the theoretical and practical experience of the selection of young volleyball players and the technology of improving their technical and tactical skills. Young athletes train in stages. During training, young volleyball players master the elements of volleyball technique and tactics, develop their physical qualities. At the same time, young athletes are trained spiritually, morally and spiritually.